MAIZENA SEBAGAI ALTERNATIF PENGGANTI PEKTIN DALAM PEMBUATAN SELAI BELIMBING (Averrhoa carambola L.) - Sari, Milya (IAIN Batusangkar, 2011)
The aim of the research was to find out the concentration of corn flour added the star fruit jam in order to increase its quality. This was an experiment designed randomly (RAL) with five treatments and three trials consisting of different concentration of corn flour addition, that is: A (0%), B (5%), C (10%), D (15%), and E (20%). The analysis, conducted after letting the jam remain in 48 hours, focused on the level of water and sugar, as well as organoleptic tests on the level of color, flavor, aroma, and texture. As the result, the addition of corn flour with different concentration effects obviously on the quality of the star fruit jam. The highly qualified jam was found at the treatment B (corn flour concentration 5%) with water level 30.05%, sugar 63.75% and organoleptically accepted.Key words: maizena, quality of corn flour